DESIGN OF CARBON MONOXIDE (CO) MEASUREMENT TOOL USING SIM900A AND SOLAR PANEL BASED ON WEMOS D1 MINI - Annisa, Risa; Saleh, Khairul; Bahtiar , Muhamad Rizki; Muallifah, Naqiyatun (Indonesian Physical Review, 2024)
With abundant natural resources, East Kalimantan has a major environmental issue: forest fires. Several cases in East Kalimantan currently garner pros and cons regarding relocating Indonesia's new capital to the region. Fires in peatlands are usually dominated by smoldering processes, resulting in the highest emissions of carbon monoxide (CO) particles. Carbon monoxide gas is odorless, colorless, and tasteless, making it difficult to detect, yet highly toxic, and can cause illness in humans. Considering the dangers caused by CO gas, this research aims to create a CO gas detector to determine air pollution conditions in the environment. This research uses an MQ-7 sensor to detect CO gas, where the data is processed into parts per million (ppm), Wemos D1 Mini as the microcontroller, and SIM900A module as the data transmitter to the website. The system uses solar panels to fulfill its power needs independently. The device's characteristics can measure CO levels ranging from 51.55 to 907.61 ppm with an average accuracy rate of 95.10% and precision of 97.18%. The model performed well overall.